Beam Hopping Beam Optimization and Resource Allocation Algorithm Based on Phased Array - Mengting HAO; Chen ZHANG; Gengxin ZHANG (天地一体化信息网络)
Beam hopping technology can provide enough fl exibility and high resource utilization for satellite communication system, and shows good performance in broadband satellite communication system.However, the existing beam planning scheme of beam hopping technology is relatively fi xed and can not change with the change of service demand characteristics.For the situation of uneven distribution of user demand and scattered location, the advantages of beam hopping technology are diffi cult to play.To solve the above problems, a beam optimization method was proposed, which used the agility characteristics of phased array antenna to adjusted the size of beam according to the characteristics of service distribution, so as to made the service demand in each beam more balanced.On this basis, from the perspective of matching the demand with the actual transmission capacity, the minimization n-order diff erence objective function was established, the time slot resources allocated in each beam were solved by convex optimization algorithm, and the overall satisfaction and system delay of the system before and after beam optimization were compared.The simulation results showed that compared with the traditional beam planning scheme, the algorithm could improved the overall satisfaction of the system, reduced the system delay and improved the access success rate of the users.